Fishing boats at dock and anchor at Harbor Wharf number 2, Fisherman's Wharf, - Albert Walton DeRome:::Creator::::::::::::
Lampara and skiffs at dock and anchor at Harbor Wharf number 2, Fisherman's Wharf, near Booth's Cannery in Monterey, California. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.)